Braneworld gravity within non-conservative gravitational theory - Fabris, J. C.; Caramês, Thiago R. P.; da Silva, J. M. Hoff [UNESP] (Springer Nature, 2018)
We investigate the braneworld gravity starting from the non-conservative gravitational field equations in a five-dimensional bulk. The approach is based on the Gauss–Codazzi formalism along with the study of the braneworld consistency conditions. The effective gravitational equations on the brane are obtained and the constraint leading to a brane energy-momentum conservation is analyzed.